OPTIMIZATION OF PAINT PRODUCT DISTRIBUTION COSTS USING THE VOGEL'S APPROXIMATION METHOD AT A NATIONAL BUILDING MATERIALS RETAIL COMPANY - Ratih Setyo Rini; Rani; Faizal Roni; Eva Zuraidah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
In the building materials retail sector, inefficient distribution practices can significantly undermine a company’s profitability. If delivery routes are not planned well, logistics costs will go up and the company becomes less competitive. This study looks at how Vogel’s Approximation Method (VAM) can help a national retailer save money on distributing paint products. By looking at the data for 2,700 units sent from three warehouses to three locations, the VAM method proved it could find the most economical way to ship goods. The result showed that shipping costs could be cut down to just IDR 3,903,000 per period. This proves that VAM is a reliable tool for managers to make smarter and more efficient distribution decisions.